PENGUKURAN RISIKO PENYALURAN KREDIT DI BANK PERKREDITAN RAKYAT - Bhinandi, Ardito (Jurnal Ekonomi & Studi Pembangunan, 2011)
Abstarct: The aim of this study is to measure the credit risk problem at BPR ABC inYogyakarta Special Region. The analysis instruments are descriptive statistics and probability.There are nine important findings result from the measurement of credit risk in BPRABC. First, gender differences customers can not be used as a primary consideration in theassessment of credit worthiness, because it has nothing to do with the smoothness of creditpayment. Second, BPR ABC as other microfinance institutions channels credit to most smallbusinesses, because it has the lowest risk. Third, low interest loans rather than loan guaranteeslow risk. Fourth, the high ratio of value of collateral and credit score is not a measure to ensure that the loans extended lower risk. Fifth, trade, hotels and restaurants have relatively low credit risk. Sixth, the more liquid a type of collateral, lower the risk. Seventh, the agreement witnessed by a notary to have a lower risk than the agreement without a notary. Eighth, the farther location cause the greater credit risk customers. Ninth, the shorter the period of credit payment, the lower the risk. Abstrak: Tujuan penelitian ini adalah mengukur masalah risiko kredit BPR ABC di DaerahIstimewa Yogyakarta. Alat analisis yang digunakan adalah statistik deskriptif dan probabilitas.Ada sembilan temuan penting hasil dari pengukuran risiko kredit di BPR ABC. Pertama,perbedaan gender pelanggan tidak dapat digunakan sebagai pertimbangan utama dalam penilaian kelayakan kredit, karena tidak ada hubungannya dengan kelancaran pembayaran kredit. Kedua, BPR ABC seperti halnya lembaga mikro keuangan lainnya yang memberikan kredit untuk sebagian besar bisnis kecil, karena memiliki risiko yang rendah. Ketiga, rendahnya bunga kredit bukan jaminan kredit tersebut risikonya rendah. Keempat, tingginya rasio nilaijaminan dengan nilai kredit bukan ukuran yang menjamin kredit yang disalurkan berisikolebih rendah. Kelima, perdagangan, hotel, dan restoran memiliki risiko kredit relatif rendah.Keenam, jaminan yang lebih likuid, risikonya lebih rendah. Ketujuh, lokasi yang lebih jauhmenyebabkan risiko yang lebih besar. Kesembilan, periode pembayaran kredit yang lebih pendek maka risikonya lebih rendah.